Novel homozygous frameshift insertion variant in the last exon of the EDARADD causing hypohidrotic ectodermal dysplasia in two siblings: case report and review of the literature - Ahmet Kablan; Elifcan Tasdelen (BMC, 2024)
Abstract Background Hypohidrotic ectodermal dysplasia (HED) is a genetic disorder that results in the abnormal development of structures derived from ectodermal tissue. This rare condition predominantly affects the hair, nails, eccrine glands, and teeth. While HED can be caused by various genes, the EDA, EDAR, EDARADD, and WNT10A genes account for approximately 90% of cases. Notably, HED forms associated with variants in the EDA, EDAR, or EDARADD genes may exhibit similar phenotypes due to defects in a common signaling pathway. Proper interaction among the products of these genes is crucial for the activation of the nuclear factor (NF-κB) signaling pathway, which subsequently regulates the transcription of targeted genes. The EDARADD gene, in particular, harbors one of the rarest reported variants associated with HED. Case presentation Five-and two-years-old brothers born into consanguineous parents were examined at our outpatient medical genetics clinic at Sanliurfa Training and Research Hospital, Turkey. Both displayed the same classical phenotypic features of HED. The elder had a very sparse dark and brittle hair, sparse eyebrows and eyelashes, conical upper and lower premolar teeth with hypodontia, widely spaced teeth, very dry skin, mildly prominent forehead, and periorbital wrinkles. The younger one showed the same, but less severe, clinical features. After thorough examination and patient history evaluation, targeted next-generation sequencing analysis yielded the novel homozygous insertion variant c.322_323insCGGGC p.(Arg108ProfsTer7) in EDARADD. The mutation has not been reported to date in the literature. Conclusions In this report, we present two siblings exhibiting classical HED symptoms and a novel insertion variant of the EDARADD gene, which leads to a frameshift introducing a stop codon. Both brothers inherited such mutation from their parents, who were heterozygous carriers of the same variant. The present study may shed light about the pathogenic mechanisms underlying HED, and expand the spectrum of EDARADD gene variants associated with this condition.